2015
DOI: 10.1017/s0142716415000338
|View full text |Cite
|
Sign up to set email alerts
|

Lexical restructuring in preliterate children: Evidence from novel measures of phonological representation

Abstract: There is substantial debate in the literature surrounding the development of children's phonological representations (PRs). Although infant studies have shown children's representations to contain fine phonetic detail, a consensus is yet to be reached about how and when phonemic categories emerge. This study used novel implicit PR measures with preschool children (n = 38, aged 3 years, 6 months to 4 years, 6 months) to test predictions made by these competing accounts of PR development. The measures were desig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 61 publications
1
25
0
2
Order By: Relevance
“…Similarly, these results suggest that when discussing changes in the importance of a predictor variable, vocabulary size is a better indicator of development than age (e.g. Ainsworth, Welbourne, & Hesketh, 2016). High phonological neighbourhood density, for instance, becomes a less important predictor of word production when expressive vocabulary size rather than age per se increases.…”
Section: Discussionmentioning
confidence: 77%
“…Similarly, these results suggest that when discussing changes in the importance of a predictor variable, vocabulary size is a better indicator of development than age (e.g. Ainsworth, Welbourne, & Hesketh, 2016). High phonological neighbourhood density, for instance, becomes a less important predictor of word production when expressive vocabulary size rather than age per se increases.…”
Section: Discussionmentioning
confidence: 77%
“…Although the term phonological representations -i.e. representations of phonological units, encompassing phonemes -has been much used, it is difficult to find measures probing phonological representations independently of other cognitive skills (Ainsworth, Welbourne, & Hesketh, 2016;Boada & Pennington, 2006) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, our longitudinal study provided the first evidence that it is possible to detect neurophysiological differences in the LPC between children with dyslexia and control children in both preliterate and very early stages of reading acquisition. The post-hoc analysis showed that differences in the access to the phonological lexicon between the control and dyslexia group already exist in kindergarten, where previous studies support the existence of a phonological lexicon before literacy acquisition ( Ainsworth et al, 2016 , Yeh et al, 2015 ). Thus, LPC attenuation in young children might be understood as an early candidate predictor of later reading problems, before the start of formal reading instruction.…”
Section: Discussionmentioning
confidence: 70%